Pengaruh Financial Literacy dan Kualitas Pendidikan Terhadap Sistem Keuangan Desa (SISKEUDES) (Studi Kasus pada Desa Pajarakan Kulon, Desa Ketompen dan Desa Selogudig Wetan Kabupaten Probolinggo) - Ubaidillah, Muhammad Fais; Askandar, Noor Shodiq; Mahsuni, Abdul Wahid (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The Education and Financial Literacy factor is very important in relation to the Village Financial System (SISKEUDES), because it enables the effective management of Village Funds by having high educational standards and a thorough understanding of financial literacy. The purpose of this study is to understand the impact of financial literacy and the quality of education on the Village Financial System, to determine the impact of financial literacy on the Village Financial System, to determine the impact of Education Quality on the Village Financial System. This study uses a quantitative method that uses statistical methods to analyze numerical data in the form of arrays (numbers). The results of this study indicate that the variables of financial literacy and quality of education have a significant effect on the local government financial system in the villages of Pajarakan Kulon, Ketompen, and Selogudig Wetan in Probolinggo Regency. This is because financial literacy and good quality education can result in safe and effective money management as well as the ability to understand new information quickly so that the distribution of assistance to rural areas can run smoothly using their local financial system and facilitate understanding and use of the special features of Siskeudes concerned to their local government officials. Keywords: Education quality, Financial Literacy, SISKEUDES